Relationship between baseline and changed serum uric acid and the incidence of type 2 diabetes mellitus: a national cohort study - Wang, Congzhi; Wang, Jiazhi; Wan, Rui; Yuan, Ting; Yang, Liu; Zhang, Dongmei; Li, Xiaoping; Wang, Min; Liu, Haiyang; Lei, Yunxiao; Wei, Huanhuan; Li, Jing; et al. (Frontiers in Public Health, 2023)
Objective: To explore the correlation between baseline serum uric acid (SUA) and SUA changes with the incidence of Type 2 diabetes mellitus (T2DM) among middle-aged and older individuals. Method: Binary logistic regression was used to calculate the odds ratio (ORs) and 95% confidence intervals (CIs) of baseline and changes of SUA on the incidence of T2DM. Stratified analysis was conducted based on sex, and the SUA levels were classified into four quartiles to assess the effect of baseline and relative changes of SUA on the incidence of T2DM. Further, interaction analysis was performed between body mass index (BMI) and SUA, age and SUA, and sex and SUA. Results: In the cohort study, the highest quartiles of SUA were significantly correlated with an increased incidence of T2DM among females in model 1 [OR=2.231 (1.631, 3.050)], model 2 [OR=2.090 (1.523, 2.867)], model 3 [OR=2.075 (1.511, 2.849)], and model 4[OR=1.707 (1.234, 2.362)]. The highest quartiles of SUA had a statistically significant effect on the incidence of T2DM among all participants in model 1 [OR =1.601 (1.277, 2.008)], model 2 [OR =1.519 (1.204, 1.915)], model 3 [OR =1.597 (1.257, 2.027)], and model 4 [OR =1.380 (1.083, 1.760)]. Regarding the relative change of SUA, the highest quantiles of SUA were significantly correlated with increased incidence of T2DM among females in model 1 [OR =1.409 (1.050, 1.890)], model 2 [OR=1.433 (1.067, 1.926)], and model 3 [OR =1.420 (1.056,1.910)], and there was a statistically significant correlation with incident T2DM among all participants in model 4 [OR =1.346 (1.079, 1.680)] after adjust all covariates. However, there was no significant correlation between baseline, relative, and absolute changes in SUA and the incidence of T2DM among males. The interaction analysis demonstrated that sex, BMI, and the relative changes of SUA had a combined effect on the incidence of T2DM, while age and the changes in SUA had a joint effect on the incidence of T2DM only in females. Conclusion: There was a positive association between SUA and the incidence of T2DM for all participants. However, significant sex differences in incidence were observed only in women, not men.